Assessing Demographics-Based Differences in Attitude Toward Honor Killings - Huda, Sadia (Journal of interpersonal violence, 2022)
The current study has been conducted to explore demographics-based differences in assessing attitudes toward honor killing. The scale used to measure attitudes is a newly developed indigenous measure. The scale consists of two subscales as follows: (a) affirmation of honor killing and (b) deterrence of honor killing. The sample comprised 695 individuals (248 males and 447 females) with ages ranging from 18 to 55 years (M?=?25.89, SD?=?8.10). The sample was collected from the federal capital city of Pakistan and various cities of Punjab (Pakistan). The results of the study found nonsignificant gender differences in the attitudes toward honor killings. Furthermore, people living in rural setups showed more affirmation than people living in urban setups. Likewise, older adults showed more affirmation to honor killing than adults of younger age groups. Finally, participants belonging to a joint/extended family system were more affirmative and had acceptance toward honor killing than those who belonged to nuclear families. Hence, the findings of the current study suggest that demographic variables play a role in determining and shaping the attitudes and beliefs of individuals regarding the phenomenon of honor killing.